The Experience and Motivations of Midwives of Color in Minnesota: Nothing for Us Without Us. (4th August 2019) - Almanza, Jennifer; Karbeah, J'Mag; Kozhimannil, Katy B.; Hardeman, Rachel
Abstract : Introduction: Racial disparities in birth outcomes originate with a confluence of factors including social determinants of health, toxic stress, structural racism, and barriers to engaging, high‐quality perinatal care. Historically and currently, midwives are disproportionately white, and attention to the racial and ethnic diversity of midwives is an increasing focus in birth equity efforts. This qualitative study helps fill the gap in literature by assessing the perspectives and motivations of midwives of color. Methods: Building on concepts from critical race theory, semistructured interviews (30‐90 minutes long) were used to elicit an authentic voice from midwives of color, who primarily identified as African American. Participants (N = 7) were midwives who were affiliated with an African American‐owned birth center in north Minneapolis, Minnesota. Participants represented an estimated 58% of all midwives of color in the state of Minnesota. Emergent themes were identified using a grounded theory, inductive approach. Three rounds of coding were conducted, and key themes were identified and analyzed. Results: Three primary themes emerged as motivations for midwives of color: 1) offering racially concordant care to the community, 2) racial justice as a primary motivation in their work, and 3) providing physically and emotionally safe care. Racially concordant care was identified both as a motivating factor and as a way of providing physically and emotionally safe care. Discussion: Findings suggest that midwives of color maintain a critical analysis of and commitment to eliminating racial perinatal inequities. Their motivation to provide racially concordant care elicits an urgency in current efforts to recruit and train more midwives of color, recognizing the current lack of racial and ethnic diversity in the field. Understanding how to support the work of equity‐minded midwives of color may help to improve access to racially concordant health care providers and care that better meets the unique needs of African American individuals.